The Communication Strategy of Ulama in Propagating the Tale of the Sabil War Against the Dutch in 1902-1912 - Riski Amal (Master Program of Sociology, Universitas Malikussaleh,, 2025)
This study examines the communication strategies employed by the ulama in propagating the Hikayat Perang Sabil during the Aceh War against the Dutch from 1902 to 1912. The Hikayat Perang Sabil was a powerful literary work that inspired the Acehnese people to resist colonial occupation, framing their struggle as a jihad (fī sabīlillāh). The research aims to identify the strategies used by the ulama, assess the effectiveness of the Hikayat Perang Sabil as a propaganda medium, and analyze the factors that influenced its impact on Acehnese society. This research employs a qualitative approach combined with historical methods, utilizing library research, document analysis, and content analysis. Primary data include manuscripts of the Hikayat Perang Sabil written by Tgk. Chik di Pante Kulu, while secondary data consist of books, journal articles, and colonial-era records. The data are analyzed within the framework of communication theory, particularly Lasswell’s communication model and the Stimulus-Organism-Response (S-O-R) theory, to evaluate how messages were constructed, delivered, and received. The findings reveal that the ulama adopted a multi-channel communication strategy, using oral recitations, manuscripts, and religious gatherings to disseminate the Hikayat Perang Sabil. The message’s religious legitimacy, emotional appeal, and repeated delivery were key to mobilizing the population. The credibility of the ulama as religious authorities significantly enhanced the acceptance of the message, leading to widespread participation in resistance efforts. This study concludes that the ulama’s communication strategy was highly effective in reviving Acehnese morale and sustaining resistance against Dutch colonialism. The Hikayat Perang Sabil not only functioned as propaganda but also as a cultural and religious symbol that reinforced Acehnese identity and collective memory. The research contributes to communication studies by demonstrating how indigenous literature can be strategically utilized for social mobilization and offers valuable insights for contemporary applications of communication strategies in community development.